2016
DOI: 10.1136/bmjgast-2015-000056
|View full text |Cite
|
Sign up to set email alerts
|

Lower response to simeprevir and sofosbuvir in HCV genotype 1 in routine practice compared with clinical trials

Abstract: BackgroundHigh sustained virological response at 12 weeks after end of treatment (SVR12) with 12 weeks of simeprevir and sofosbuvir±ribavirin (SMV+SOF±RBV) has been demonstrated in hepatitis C virus genotype 1 (HCV-1) but is based on limited data. Therefore, we performed a meta-analysis of available data evaluating the effectiveness of SMV+SOF±RBV in HCV-1.MethodsWe performed a comprehensive literature search in June 2015 to identify randomised controlled trials (RCTs) and observational studies of HCV-1 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…In another subgroup analysis of patients with SVR12 and fibrosis data, there was a higher SVR12 rate in patients with mild fibrosis (93%) compared with those with advanced fibrosis (82%), with a trend favouring SVR12 in patients with mild fibrosis 6 14…”
Section: Discussionmentioning
confidence: 95%
“…In another subgroup analysis of patients with SVR12 and fibrosis data, there was a higher SVR12 rate in patients with mild fibrosis (93%) compared with those with advanced fibrosis (82%), with a trend favouring SVR12 in patients with mild fibrosis 6 14…”
Section: Discussionmentioning
confidence: 95%
“…37 Importantly, in this study, the interferon-free and RBV-free regimen of DCV + ASV provided SVR rate in genotype 1b infection that was slightly higher than that of a pooled analysis reported for combinations of SOF plus simeprevir with or without RBV in HCV patients with genotype 1b infection, with similar frequencies of most common AEs. 38 Therefore, on the basis of its favorable safety and high response rates with good tolerability in ineligible/intolerant and nonresponder patients with compensated cirrhosis, irrespectively of gender, race, advanced age, and non-CC IL28B genotype, DCV + ASV is a promising treatment option for this patient population, especially when genotype 1b is highly prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…In a large, real‐world observational cohort study ( N = 4365) of SOF/LDV ± RBV in HCV GT1 infection, SVR rates of 93.2% and 96.6% were reported after 8 and 12 weeks of treatment, respectively, in non‐cirrhotic treatment‐naive patients with baseline HCV RNA <6 × 10 6 IU/mL who received SOF/LDV . A recent meta‐analysis of clinical trials and real‐world observational studies evaluating the effectiveness of SMV + SOF ± RBV in patients with HCV GT1 found that SVR rates reported in observational studies were lower (84%) than those reported in randomized controlled trials (RCTs;94%) with this regimen . The French Observational Cohort ANRS CO22 HEPATHER study is designed to follow up to 15 000 HCV patients over 10 years to collect real‐world clinical data.…”
Section: Introductionmentioning
confidence: 99%
“…These findings extend to challenging patient populations, with SVR rates of 95.5% reported in chronic hemodialysis patients infected with HCV GT1 receiving DCV + ASV in another recent prospective observational study in Japan . Yet, despite these positive findings, there are relatively few real‐world studies of DAAs—particularly in Asia—and insufficient data to draw robust comparisons of real‐world and clinical trial outcomes in different patient subgroups (e.g., treatment‐naive and experienced patients, or cirrhotic and non‐cirrhotic patients) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation